Optimize Illumination Parameter of Low-Level Laser Therapy for Hemorrhagic Stroke by Monte Carlo Simulation on Visible Human Dataset - Ting Li; Pengbo Wang; Lina Qiu; Xiang Fang; Yu Shang (IEEE Photonics Journal)
Stroke is the second leading cause of death and disability worldwide. The incidence of hemorrhagic stroke increases dramatically with the increasingly aging population. Recently, technology of low-level light/laser therapy (LLLT) is emerging as a novel noninvasive therapeutic approach to treat stroke based on effective photobiomodulation. To obtain optimal therapeutic effects, several LLLT illumination parameters such as beam size and beam type need to be optimized. However, the quantitative optimization of LLLT illumination parameters for stroke therapeutics is impractical to test directly on human subjects. In this paper, we employed a precise voxelized three-dimensional Monte Carlo method (MCVM) to simulate photon propagation within Visible Chinese human (VCH) head at different level of stroke with varied parameters of beams. By evaluation with criteria of the total fluence flux in lesion region and the maximal penetration depth, we found that Gaussian beam with larger or the same size of hemorrhagic region generates the highest and relative homogeneous therapeutic outcomes, while the Top-hat beam performed better when hemorrhagic region is much bigger than beam size. These results demonstrate the great potential of using VCH and MCVM in optimizing LLLT treatment parameters for stroke and in guiding future instrumentation of LLLT on hemorrhagic stroke.